2022
DOI: 10.3390/ijerph20010653
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High-Intensity Interval Training and Continuous Aerobic Training on Health-Fitness, Health Related Quality of Life, and Psychological Measures in College-Aged Smokers

Abstract: The study examined the effects of exercise on health-fitness, health related quality of life (HRQOL), and psychological measures in college-aged smokers. Outcomes included HRQOL, hemodynamic, anthropometric, lung function, and cardiorespiratory endurance. Sixty physically inactive college-aged male smokers (18–30 years) were randomly assigned into three groups: high-intensity interval training (HIIT), continuous aerobic training (CAT), and a control (CON). Both HIIT and CAT groups completed 8 weeks of non-cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…As part of the risk factors, tobacco use and in particular, cigarette smoking is the single most preventable cause of morbidity and mortality worldwide [9,[18][19][20]. Studies have reported that in 2030, smoking rate will approximately increase by 80% of the current total population of smokers with significant contribution predominantly by college-aged smokers in rural areas [9,19,20]. Smoking results in multiple alterations on the performance of the cardiovascular system [9].…”
Section: Noncommunicable Disease (Ncd) Risk Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…As part of the risk factors, tobacco use and in particular, cigarette smoking is the single most preventable cause of morbidity and mortality worldwide [9,[18][19][20]. Studies have reported that in 2030, smoking rate will approximately increase by 80% of the current total population of smokers with significant contribution predominantly by college-aged smokers in rural areas [9,19,20]. Smoking results in multiple alterations on the performance of the cardiovascular system [9].…”
Section: Noncommunicable Disease (Ncd) Risk Factorsmentioning
confidence: 99%
“…Studies have reported that in 2030, smoking rate will approximately increase by 80% of the current total population of smokers with significant contribution predominantly by college-aged smokers in rural areas [9,19,20]. Smoking results in multiple alterations on the performance of the cardiovascular system [9]. For instance, a toxic chemical released during cigarette smoking called nicotine causes catecholamine release which triggers an increase in the heart rate, Blood Pressure (BP) and cardiac output (Q) [9,[19][20][21].…”
Section: Noncommunicable Disease (Ncd) Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…This programme followed a sequential style to implementation whereby clusters of participants began the programme in multiple phases following appropriately sensitive and cost-effective screening assessing the health-related physical fitness parameters of cardiorespiratory endurance, muscular fitness (including muscular endurance and muscular strength), body composition, flexibility, and balance [24]. Re-assessment of these parameters took place mid-programme and at completion of the programme.…”
Section: Participantsmentioning
confidence: 99%
“…Research in the physical activity adherence has resulted in the recognition of several methods to influence an uptake of physical activity at the individual level [38]. However, the considerable prevalence of inactivity across most sectors of the global population necessitates higher-level approaches to physical activity promotion that include environmental, organisational, and policy-level strategies.…”
Section: Physical Activity As a Public Health Interventionmentioning
confidence: 99%